Studies Using Salcylaldehyde Chromone Derivatives as Mixed Ligands in Preparation of some Complexes - Gadalla, Suleiman O.; Mihoub, Abdulsalam Ali (Al-Mukhtar Journal of Sciences, 2003)
Two mixed ligand complexes of salicyladehyde (L1) and 6-Formyl-7-hydroxy-5-methoxy-2-methylchromone (L2) have been prepared and characterized by using elemental analysis, molar conductance measurements and infrared spectroscopy. These complexes have the general chemical formula [ML1L2 . 2H2O] . n H2O in a ratio of M:L1:L2 (1:1:1) , where M represent Mn(II) and Co (II) and m n=2 or 6 according to the suggested chemical structure of the complexes. The molar conductance indicate that the synthesized complexes are nonelectrolytic, whereas IR spectra display that the complexation takes place through the aldehydic group in position 6 and hydroxyl group in position 7 of the chromone moiety and the same functional groups of the salicylaldehyde moiety.